Calidad nutritiva y microbiológica de colágeno extraído a partir de escamas de peces amazónicos - Panduro Sarmiento, Diego Jhonatan (2023)
The research concludes the nutritional and microbiological quality of collagen extracted from the scales of Megaleporinus trifasciatus (lisa), Prochilodus nigricans (boquichico) and Semaprochilodus insignis (yaraquí). The study had a quantitative approach of a non-experimental, descriptive type with an explanatory scope. The nutritional and microbiological bromatological analysis was obtained as techniques for obtaining data from lyophilized collagen. The results report protein values of 28.18±0.63%, 45.59±0.54%, 33.31±0.67%, lipids of 0.75±0.03%, 0.43±0.03% and 0.40±0.02%, and carbohydrates 7.44±0.20%, 45.08±0.28%, 45.05±0.0.49%, for lisa, boquichico and yaraquí respectively. With respect to vitamins and minerals, the presence of iron, zinc, calcium, sodium, potassium and vitamin "A" was found; lisa collagen reported a higher percentage of vitamin "A" (10.06 ± 0.27 μg β-carotene/g). The amino acid profile emerged from the presence of glycine (216.28±0.02 mg/g, 109.27±0.06 mg/g, and 113.97±0.02 mg/g) and proline (116.49±0.01 mg/g, 59.45±0.05 mg/g, 60.56 ±0.01 mg/g) in collagen from lisa, boquichico, and yaraqui scales. The microbiological quality reported the count of mesophiles, molds and yeasts within the permissible range, as well as the absence of the pathogen Salmonella sp. The study concludes that the nutritional and microbiological quality of the studied collagen is within the reference values, indicating the possibility of using it in the formulation of functional foods.